The Uncertain Value of Uncertainty: When Consumers Are Unwilling to Pay for What They Like - Moon, Alice; Nelson, Leif D. (Management Science, 2020)
Do people have an irrational dislike for risk? People pay less for uncertain prospects than their worst possible outcomes, and researchers have proposed that this effect occurs because people strongly dislike risk. We challenge this proposition across seven studies. Though people seem to irrationally dislike risky prospects when preference is assessed with open-ended pricing measures, such as willingness-to-pay, people display rational responses toward risky prospects when preference is assessed using rating measures, such as ratings of expected enjoyment. This discrepancy does not seem to arise because these measures (a) focus on different components of the uncertainty, (b) rely on context-dependent versus normed scales, or (c) involve voluntarily opting into an uncertain situation. Accordingly, we find that people also display rational responses toward risky prospects with time measures (i.e., willingness-to-wait and anticipated time usage) and choice. We discuss alternative explanations and crucial implications of our effects for both theory and application. This paper was accepted by Yuval Rottenstreich, judgment and decision making.